Migration law of different top coal thicknesses in top coal caving - Nan, Hua; Wang, Shuai (Frontiers in Earth Science, 2022)
Top coal caving has become one of the main mining methods for thick and extrathick coal seams. Because of coal seam conditions, the top coal thickness is not constant. It is necessary to study the influence of top coal thickness changes on the top-coal-caving mining process. To explore the migration law of top coal failure, the experimental means of similar simulation experiment, numerical simulation experiment and field monitoring data were used. Through a similar simulation test of three different top coal thicknesses, the change rule of top coal migration was analyzed. Moreover, the stress and displacement changes of a 14 m coal seam over a thick top coal caving face were monitored and analyzed comprehensively with the simulation results. The results show that when the top coal thickness is unchanged, the top coal vertical displacement in the upper part is larger than that in the middle part due to the top plate rotation in front of the working face, and the stress change follows an opposite trend. The simulation results were the same as the field test results. When the top coal thickness is changed, whether it is upper top coal or middle top coal, the top coal displacement and stress changes will increase. The top coal migration will be more obvious, and thus the crushing will be more serious.